Association between immunosuppressants and poor antibody responses to SARS-CoV-2 vaccines in patients with autoimmune liver diseases - Li, Hu; Wang, Yuting; Ao, Ling; Ke, Mingxia; Chen, Zhiwei; Chen, Min; Peng, Mingli; Ling, Ning; Hu, Peng; Cai, Dachuan; Zhang, Dazhi; Ren, Hong (Frontiers in Immunology, 2022)
The antibody and B cell responses after inactivated SARS-CoV-2 vaccination have not been well documented in patients with autoimmune liver disease (AILD). Therefore, we conducted a prospective observational study that included AILD patients and healthy participants as controls between July 1, 2021, and September 30, 2021, at the Second Affiliated Hospital of Chongqing Medical University. All adverse events (AEs) after the COVID-19 vaccination were recorded and graded. Immunoglobulin (Ig)-G antibodies against the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein (anti-RBD-IgG) and neutralizing antibodies (NAbs) were tested following full-course vaccination (BBIBP-CorV or CoronaVac). In addition, SARS-CoV-2-specific B cells were detected by flow cytometry. In total, 76 AILD patients and 136 healthy controls (HCs) were included. All AEs were mild and self-limiting, and the incidences were similar between the AILD and HCs. The seropositivity rates of anti-RBD-IgG and NAbs in AILD were 97.4% (100% in HCs, p = 0.13) and 63.2% (84.6% in HCs, p < 0.001), respectively. The titers of anti-RBD-IgG and NAbs were significantly lower in AILD patients than in HCs. After adjusting for confounders, immunosuppressive therapy was an independent risk factor for low-level anti-RBD-IgG (adjusted odds ratio [aOR]: 4.7; 95% confidence interval [CI], 1.5-15.2; p = 0.01) and a reduced probability of NAbs seropositivity (aOR, 3.0; 95% CI, 1.0-8.9; p = 0.04) in AILD patients. However, regardless of immunosuppressants, the SARS-CoV-2-specific memory B cells responses were comparable between the AILD and HC groups. Our results suggest that inactivated SARS-CoV-2 vaccines (BBIBP-CorV and CoronaVac) are safe, but their immunogenicity is compromised in patients with AILD. Moreover, immunosuppressants are significantly associated with poor antibody responses to the SARS-CoV-2 vaccines. These results could inform physicians and policymakers about decisions on screening the populations at higher risk of poor antibody responses to SARS-CoV-2 vaccines and providing additional vaccinations in patients with AILD.